Multi-soliton solutions and Breathers for the generalized coupled nonlinear Hirota equations via the Hirota method - Jia, Ting-Ting; Chai, Yu-Zhen; Hao, Hui-Qin (Superlattices and microstructures, 2017)
Under investigation in this paper is the generalized coupled nonlinear Hirota (GCH) equations with addition effects by the Hirota method, which is better than the coupled nonlinear Schrödinger equations in eliciting optical solitons for increasing the bit rates. The bilinear form has been constructed, via which multi-solitons and breathers are derived. In particular, the three-bright soliton solution and breathers are derived and simulated via some pictures. The propagation characters are analyzed with the changes of the key parameters. •The breathers, multi-solitons for the generalized coupled nonlinear Hirota equations via the Hirota method.•Three-bright soliton solutions and the propagation process of the three-soliton turning to the breather have been derived.•Dynamic features of those solitons have been analyzed.